The "professional becoming" of newly-qualified nurses in the English NHS - Roe, Bridget (2016)
This thesis develops new empirical insights on the socialisation of English National Health Service (NHS) newly-qualified nurses as they enter the workplace. The NHS continues to face financial and human resource constraints on ensuring the quality and safety of patient care. Nurses are the largest professional group within the NHS, and their recruitment and retention has been problematic which has implications for the ability of organisations to deliver high quality care. Nursing has a turbulent history where changes to education and recent scandals have also raised questions about the quality and safety of care delivered by newly-qualified nurses. Within this context, Preceptorship has been introduced to improve retention and quality by supporting the transition from education into the workforce through several months of support and blended learning. This study focuses on the implementation and operationalisation of one NHS Trusts’ Preceptorship programme.